Natamycin - antimycotic of polyene macrolides class with unusual properties - I. O. Malova; D. D. Petrunin (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
In the current literature review issues regarding physicochemical peculiarities, mechanism ot action and satety aspects ot polyene macrolides class compound natamycin are enlightened along with the extensive clinical data upon the use ot pharmaceuticals containing this active ingredient.